2016
DOI: 10.1097/01.reo.0000000000000022
|View full text |Cite
|
Sign up to set email alerts
|

Mirror Therapy for Phantom Limb Pain at a Pediatric Oncology Institution

Abstract: Background and Purpose/Objective Mirror therapy has not been reported for phantom limb pain (PLP) in pediatric oncology. Our aims are to describe the incidence and duration of PLP post-amputation, the duration of follow-up, pain scores and pain medications, and the differences between a group that received mirror therapy (MT) in addition to the standard treatment and a group that received only the standard treatment (non-MT). Methods A retrospective review of patients’ medical records from June 2009 to March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 15 publications
1
28
0
1
Order By: Relevance
“…Two studies could not be included in the meta‐analysis. A study using 15 amputees with PLP showed no significant pain reduction comparing mirror VF using a normal‐sized reflection with no treatment (SMD = −0.08; 95% CI = −1.10, 0.93, (Anghelescu et al., ). The study including six amputees with PLP showed that the combination of mirror VF using a normal‐sized reflection with synchronized stroking of the stump and the hand in front of the mirror significantly reduced pain compared with only mirror VF using a normal‐sized reflection (SMD = −1.58, 95% CI = −2.50, −0.66, (Schmalzl et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies could not be included in the meta‐analysis. A study using 15 amputees with PLP showed no significant pain reduction comparing mirror VF using a normal‐sized reflection with no treatment (SMD = −0.08; 95% CI = −1.10, 0.93, (Anghelescu et al., ). The study including six amputees with PLP showed that the combination of mirror VF using a normal‐sized reflection with synchronized stroking of the stump and the hand in front of the mirror significantly reduced pain compared with only mirror VF using a normal‐sized reflection (SMD = −1.58, 95% CI = −2.50, −0.66, (Schmalzl et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…At this time, no one medication is standard of practice, but several modalities have demonstrated benefits. In pediatric and pediatric oncology reports, medication utilization is similar to adult reports, with most authors reporting some combination of medications for treatment ( 8 , 11 , 12 ).…”
Section: Evidence-based Treatments In Pediatricsmentioning
confidence: 88%
“…For congenitally related amputations, the prevalence of PLP has been noted to be lower, between 3.7 and 20% of children, even occurring in children with congenital absence of a limb ( 4 , 10 ). In the pediatric oncology population, the prevalence of PLP is also wide ranging between 48 and 90% ( 5 , 7 , 11 , 12 ). The onset of pediatric PLP typically occurs shortly after amputation, most often within the first week after amputation ( 5 , 7 ).…”
Section: Pediatric Plp Characteristics and Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations